Liaison Between Librarians and Lecturers Regarding Information Literacy: A Case Study of Some Academic Libraries - Marga García-Bajo (Universidad de Navarra, 2009)
This research looked at the liaison between the library information professionals and academic staff of academic institutions stressing the aspect of information literacy. The general aims of this research were to emphasize the importance of training in information literacy in higher education, for students, academic staff and library staff and to stress that essential collaboration between librarians and faculty staff is basic for successful results. The research method used to collect data was the interview. Interviews were conducted with both librarians and lecturers at Thames Valley University and at some colleges of the University of London